Optimalisasi Pelatihan Kepenulisan Dalam Meningkatkan Karya Ilmiah Mahasiswa IAT Universitas Yudharta Pasuruan di Pondok Pesantren LSQ Ar-Rahmah - Kurniawan, Rizki; Shodiq, M. Ja’far; Rochma, Nur; Husna, Shofiatul; Anwariyah, Khusnul; Silviana, Ita; Zainuddin, Ahmad (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
The field experience practice conducted by students from Yudharta Pasuruan University aims to improve scientific work skills, carried out through writing training held at the LSQ Ar-Rahmah Islamic boarding school, Bantul, Yogyakarta. The background of this activity is expected that students of the Qur'an and Tafsir Sciences of Yudharta Pasuruan University can produce quality scientific works at the student level in order to support preparation for making proposals and theses. We can see that students are currently minimal in making scientific works, even though the skills that a student must have are in the field of correct writing and according to the flow of making. Therefore, this PPL activity for students of the Qur'an and Tafsir Sciences of Yudharta Pasuruan University is expected to be more accurate in producing scientific works through writing training at the LSQ Ar-Rahmah boarding school. The method used is direct training and intensive mentoring from mentors at the LSQ Ar-Rahmah Bantul boarding school, Yogyakarta. This writing training was carried out for approximately 2 weeks. Students are required to create scientific works in the form of journal articles output from this PPL activity, it is expected that the journal can be included in the synta and successfully published. The results of the activity show an increase in skills and the emergence of new interests among students to be more enthusiastic in creating scientific works.